Economic valuation of seagrass ecosystem in Maribojoc Bay, Bohol, Philippines (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mascari?as HJC, Otadoy JB. 2023. Economic valuation of seagrass ecosystem in Maribojoc Bay, Bohol, Philippines. Biodiversitas 24: 4427-4435. The seagrass ecosystem is one of the most productive and precious ecosystems. In the Philippines, however, more data on the economic valuation of all seagrass ecosystem services must be collected. The study estimated the total economic value of the seagrass ecosystem, including use and non-use values. Resource user groups include municipal ?shers, gleaners, and tourism business operators. The sample size was determined based on the total number of resource users in Maribojoc Bay, Bohol, Philippines and using a confidence coefficient of 95% (P = 0.05). The total economic value of the seagrass ecosystem in Maribojoc Bay is PhP 52.8 million (US$ 1.1 million). Direct use values, or market benefits, are PhP 35.4 million (US$ 708 thousand), accounting for 67% of the total economic value. Indirect and non-use values, are PhP 17.3 million (US$ 346 thousand), accounting for 33% of the total economic value. On a per hectare basis, the economic value of the seagrass ecosystem in Maribojoc Bay is PhP 46,722 (US$ 934). The results of this valuation can be an input in decision-making to manage and conserve the seagrass ecosystem as well as maintain the economic security of Maribojoc Bay. The findings of this study are valuable for developing a comprehensive information management and decision-support system for the management and protection of the seagrass ecosystem. However, more research is required to evaluate the range of ecosystem services provided by seagrass ecosystems across the country, focusing on qualitative value attributions linked to the social-ecological dynamics of seagrass systems.
Keywords: Economic values, ecosystem services, Maribojoc Bay, seagrass valuations